2022
DOI: 10.1016/j.amsu.2021.103234
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of gastrointestinal manifestations in COVID-19 Egyptian patients

Abstract: Background The latest novel corona virus disease (COVID-19) pandemic shows a significant health concern. We aimed to study the prevalence of gastrointestinal symptoms among COVID-19 Egyptian patients. Methods A cross-sectional study was carried out on 860 patients with COVID-19 infection classified according to Ministry of Health Program (MOHP) into three groups (280 patients with mild disease, 258 patients with moderate disease and 322 patients with severe disease). Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
2
7
1
Order By: Relevance
“…Our data are in line with other similar studies in the literature [12][13][14][15][16][17][18][19][20][21][22]. Those studies, mainly performed in the USA, showed a significant association between the increase in liver function and disease progression or death in patients with COVID-19 [20][21][22].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data are in line with other similar studies in the literature [12][13][14][15][16][17][18][19][20][21][22]. Those studies, mainly performed in the USA, showed a significant association between the increase in liver function and disease progression or death in patients with COVID-19 [20][21][22].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the increase in bilirubin levels at time of hospital admission is significantly related to hospital mortality; however, also considering the minor association, further research is required to validate the data shown. Considering the need for tools and prognostic examinations that can help to predict the clinical progression of disease in COVID-19 patients, our study, with others recently published [8][9][10][11][12][13][14][15][16][17][18][19], could be a useful guide, using liver damage and liver function tests to highlight patients at risk of COVID-19 progression or to predict the severity of disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within our cohort, 104 (34.7%) patients presented with GI symptoms which is lower than the results reported by other studies conducted in the USA and China which were in the range of 50.5-61.3% [10,12]. In contrast, this prevalence was higher than other studies conducted in China, Italy, and Egypt [7,22,24,25].…”
Section: Discussioncontrasting
confidence: 83%
“…On the contrary, Hegazy, and colleagues, 2021 conveyed that patients with mild symptoms who present with diarrhea and duration of symptoms longer than 12 days are expected to have a worse prognosis [23]. Moreover, Teimaa and his associates, 2022 found that the presence of associated gastrointestinal symptoms in COVID19 infection patients reflected the severity of the infection [24]. In summary, Sulaiman and his colleagues, 2020 reported that the presence of COVID19related gastrointestinal symptoms alone carried a better prognosis while their presence with respiratory symptoms was associated with higher morbidity and mortality [25].…”
Section: Discussionmentioning
confidence: 99%